1986
DOI: 10.1111/j.1745-4557.1986.tb00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Restructured Steaks Manufactured From Pre‐rigor Beef of Varying Particle Size

Abstract: Raw materials were removed from U.S. Choice Yield Grade 3 beef forequarters I h postmortem. Samples were jlaked with an Urschel Comitrol3600 as three sizes; small (head opening = 3.0 mm), medium (head opening = 6. I mm) and large (head opening = 9.9 mm). Each flake size was formulated with I . 0% NaCl and 0.25 % sodium tripolyphosphate (STP), converted into 25 mm thick restructured steaks and packaged. Subjective evaluations were conducted a$er 0 and 56 days of frozen storage for color, cohesiveness, muscle cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Instrumental tenderness measurements confirm this hypothesis that less force was needed to deform tumbled meat (Judge and Cioch, 1979;Chow et al, 1986), but sensory results diverge on this subject (Bedinghaus et al, 1992). Marriott et al (1986) reported that particle size had no effect on flavor and juiciness of restructured pork but tenderness was decreased as the particle size increased from 3 to 9.9 mm. Furthermore they found an increase in connective tissue detected by panelists with the larger particle size.…”
Section: Sensory Qualitysupporting
confidence: 48%
See 1 more Smart Citation
“…Instrumental tenderness measurements confirm this hypothesis that less force was needed to deform tumbled meat (Judge and Cioch, 1979;Chow et al, 1986), but sensory results diverge on this subject (Bedinghaus et al, 1992). Marriott et al (1986) reported that particle size had no effect on flavor and juiciness of restructured pork but tenderness was decreased as the particle size increased from 3 to 9.9 mm. Furthermore they found an increase in connective tissue detected by panelists with the larger particle size.…”
Section: Sensory Qualitysupporting
confidence: 48%
“…The particle sizes of 2.5 and 5.0 mm in pre-rigor and aged beef steaks were studied by Seideman et al (1982) and it was indicated that larger particle sizes were associated with lower texture desirability ratings and less tender beef steaks. Marriott et al (1986) showed that particle size had a minimal effect on muscle cut resemblance, cooking loss, shear value and sensory attributes. Berry et al (1987) indicated that thickness of the flake particle was as important as width of the flake particle in affecting texture.…”
Section: Effect Of Meat Particle Size In Restructured Productmentioning
confidence: 99%
“…The results indicated that KCl and CaCl 2 were more desirable than NaCl. Marriott et al (1986a) found that in relation to the reduction in color and flavor, the storage time and the presence of salt were more critical than the grade of salt.…”
Section: Role Of Non-meat Ingredients Saltmentioning
confidence: 99%
“…Berry, Smith, and Secrist (1987) indicated that thickness of the flake particle was as important as width of the flake particle in affecting texture. Marriott, Phelps, Costello, and Graham (1986a) showed that particle size had a minimal effect on muscle cut resemblance, cooking loss, shear value, and sensory attributes.…”
Section: Particle Sizementioning
confidence: 99%
“…Restructured beef steaks made with the larger particle size were tougher than beef steaks processed with smaller particle sizes. Marriott et al (1986) and Chesney et al (1978) previously reported that smaller particle sizes were more cohesive than larger particle sizes. This result was not verified by the present study.…”
Section: Ns Amentioning
confidence: 91%